2021
DOI: 10.3390/ani11113212
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification and Comparison of the Expressed Profiles of lncRNAs, miRNAs, circRNAs, and mRNAs with Associated Co-Expression Networks in Pigs with Low and High Intramuscular Fat

Abstract: Intramuscular fat (IMF) content is a complex trait that affects meat quality and determines pork quality. In order to explore the potential mechanisms that affect the intramuscular fat content of pigs, a Large white × Min pigs F2 resource populations were constructed, then whole-transcriptome profile analysis was carried out for five low-IMF and five high-IMF F2 individuals. In total, 218 messenger RNA (mRNAs), 213 long non-coding RNAs (lncRNAs), 18 microRNAs (miRNAs), and 59 circular RNAs (circRNAs) were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
(71 reference statements)
0
7
1
Order By: Relevance
“…Therefore, the present study assessed the circRNA expression patterns in the longissimus dorsi muscle using RNA-seq and identified 336 circRNAs DE between pigs with high and low content of IMF, suggesting their role in porcine IMF deposition. The circRNAs identified in this study and found to be DE between the pigs with different IMF levels are more than those in the previous reports. , This observation suggests that the circRNAs regulating IMF content in pigs has not been comprehensively explored, and thus, additional mechanisms regulating IMF deposition remain elusive.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Therefore, the present study assessed the circRNA expression patterns in the longissimus dorsi muscle using RNA-seq and identified 336 circRNAs DE between pigs with high and low content of IMF, suggesting their role in porcine IMF deposition. The circRNAs identified in this study and found to be DE between the pigs with different IMF levels are more than those in the previous reports. , This observation suggests that the circRNAs regulating IMF content in pigs has not been comprehensively explored, and thus, additional mechanisms regulating IMF deposition remain elusive.…”
Section: Discussioncontrasting
confidence: 54%
“…The circRNAs identified in this study and found to be DE between the pigs with different IMF levels are more than those in the previous reports. 12,60 This observation suggests that the circRNAs regulating IMF content in pigs has not been comprehensively explored, and thus, additional mechanisms regulating IMF deposition remain elusive. In addition, certain circRNAs function as competitors of their linear RNAs, influencing host gene expression levels.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In chickens, lncRNA IMFNCR promotes intramuscular adipocyte differentiation by sponging miR-128-3p and miR-27b-3p [ 81 ]. Generally, ncRNA regulates the expression of targeted mRNAs [ 80 ]; for example, Cheng et al (2021) identified DE lncRNAs, miRNAs, circRNAs, and mRNAs and constructed multiple ceRNAs which play an important role in the complex molecular processes of IMF deposition between large white × Min crossbred pigs [ 82 ]. Previous studies have reported that miR-381-3p plays a positive role in adipogenic differentiation of adipose-derived stem cells [ 83 ], obesity-related diseases (type 2 diabetes) [ 84 ], and sheep muscle growth and development [ 85 ] by regulating target genes.…”
Section: Discussionmentioning
confidence: 99%